PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS PENDEKATAN CULTURALLY RESPONSIVE TEACHING MATERI KERAGAMAN BUDAYA INDONESIAKU UNTUK SISWA KELAS V SD - Fadhilla Berliana; Ahmad Syarif; Muhammad Sholeh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The primary objective of this investigation was to design and construct interactive multimedia materials embedded with a Culturally Responsive Teaching (CRT) framework focusing on Indonesian Cultural Diversity for fifth-grade primary school classrooms. The inquiry was prompted by the current pedagogical gap regarding the underutilization of tech-based learning tools that can seamlessly embed regional cultural heritage into Pancasila Education courses. Implementing localized, authentic learning experiences that resonate with students' daily lives is critical for fostering classroom engagement and strengthening conceptual comprehension of national cultural pluralism. This study applied a Research and Development (R&D) framework utilizing the sequential ADDIE model, which encompasses the analysis, design, development, implementation, and evaluation phases. Empirical data were gathered via direct field observations, structured interviews, and evaluative questionnaires. The analytical findings reveal that the newly developed interactive multimedia successfully met the rigorous standards of being highly valid and exceptionally practical for daily instructional purposes. Merging indigenous cultural values into the digital multimedia framework effectively generated a more captivating, participatory, and contextualized academic environment, which in turn helped young learners grasp the nuances of cultural diversity with greater ease. The educational implications of this research indicate that CRT-driven interactive multimedia represents a highly viable alternative tool to reinforce students' cultural identities, amplify learning enthusiasm, and assist educators in orchestrating more substantial, high-impact learning experiences within elementary education. ABSTRAK Target utama dari kajian ini adalah untuk merancang produk multimedia interaktif yang mengadopsi model Culturally Responsive Teaching (CRT) pada unit materi Keragaman Budaya Indonesiaku bagi audiens siswa kelas V Sekolah Dasar. Riset ini didorong oleh realitas di lapangan mengenai minimnya pemanfaatan perangkat pembelajaran berbasis teknologi digital yang mampu menyelaraskan unsur kebudayaan lokal ke dalam kurikulum Pendidikan Pancasila. Padahal, formulasi pembelajaran yang bersifat aplikatif serta akrab dengan realitas harian siswa sangat dibutuhkan guna menstimulasi partisipasi aktif serta mempertajam pemahaman mereka mengenai pluralitas kultural di Indonesia. Metode yang diterapkan dalam penelitian ini adalah Research and Development (R&D) dengan bersandar pada kerangka ADDIE, yang tahapannya meliputi fase analisis, perancangan, pengembangan, implementasi, serta evaluasi. Proses penghimpunan data mengandalkan teknik pengamatan langsung, wawancara, dan pengisian lembar kuesioner/angket. Hasil uji lapangan membuktikan bahwa perangkat multimedia interaktif yang diproduksi telah memenuhi standardisasi dengan predikat sangat valid sekaligus sangat praktis untuk diaplikasikan dalam kegiatan kelas. Internalisasi komponen tradisi lokal ke dalam sistem multimedia terbukti sukses melahirkan impresi belajar yang lebih memikat, dua arah, serta membumi, sehingga mempermudah peserta didik dalam menguasai topik keragaman budaya. Implikasi dari penelitian ini menegaskan bahwa pemanfaatan multimedia interaktif berorientasi CRT layak dijadikan opsi instrumen ajar yang efektif untuk memperkokoh jati diri kultural siswa, menaikkan fokus belajar, sekaligus memandu guru dalam menciptakan iklim pembelajaran yang lebih bernilai di tingkat sekolah dasar.